2022
DOI: 10.1038/s41467-022-33569-2
|View full text |Cite
|
Sign up to set email alerts
|

Location bias contributes to functionally selective responses of biased CXCR3 agonists

Abstract: Some G protein-coupled receptor (GPCR) ligands act as “biased agonists” that preferentially activate specific signaling transducers over others. Although GPCRs are primarily found at the plasma membrane, GPCRs can traffic to and signal from many subcellular compartments. Here, we determine that differential subcellular signaling contributes to the biased signaling generated by three endogenous ligands of the GPCR CXC chemokine receptor 3 (CXCR3). The signaling profile of CXCR3 changes as it traffics from the p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 79 publications
1
18
0
Order By: Relevance
“…However, at the endosome, only CXCL11 was able to recruit β-arrestin, while all three ligands still maintained G protein activation. [12] Similar findings were obtained in the study on the AT1R, where the authors found that inhibiting internalization had a significant impact on a ligand's ability to recruit β-arrestin, but did not impact G protein activation. [79] It is plausible that these observations occur due to differential localization and availability of G proteins and β-arrestins in subcellular compartments.…”
Section: The Interaction Between Location-specific and Biased Gpcr Si...supporting
confidence: 80%
See 4 more Smart Citations
“…However, at the endosome, only CXCL11 was able to recruit β-arrestin, while all three ligands still maintained G protein activation. [12] Similar findings were obtained in the study on the AT1R, where the authors found that inhibiting internalization had a significant impact on a ligand's ability to recruit β-arrestin, but did not impact G protein activation. [79] It is plausible that these observations occur due to differential localization and availability of G proteins and β-arrestins in subcellular compartments.…”
Section: The Interaction Between Location-specific and Biased Gpcr Si...supporting
confidence: 80%
“…[41][42][43] Subsequent work demonstrated endosomal activation of Gαs, Gαi/o, and Gαq at a diverse array of GPCRs. [12,[44][45][46] GPCRs which activate the Gαs subunit and exhibit receptor signaling from endosomes have demonstrated sustained and consequential cAMP signaling upon receptor internalization. [43,[47][48][49][50] Additionally, endosomal cAMP production has been shown to promote nuclear cAMP and PKA activation in ways that cAMP generated at the plasma membrane cannot.…”
Section: The Role Of β-Arrestins and G Proteins In Gpcr Signaling Fro...mentioning
confidence: 99%
See 3 more Smart Citations